(untitled) (Diametros, 2019)
The present paper investigates the question of whether right-libertarians must accept easements by necessity. Since easements by necessity limit the property rights of the owner of the servient tenement, they apparently conflict with the libertarian homestead principle, according to which the person who first mixes his labor with the unowned land acquires absolute ownership thereof. As we demonstrate in the paper, however, the homestead principle understood in such an absolutist way generates contradictions within the set of rights distributed on its basis. In order to avoid such contradictions, easements by necessity must be incorporated into the libertarian theory of property rights and the homestead principle must be truncated accordingly.